The perpetual magic formula: time, colonialism and repetition in the writing of history - Rufer, Mario (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article analyzes the connection of the modern writing of history with the domination of the conqueror, the sovereignty imposed by war and the concealment of this connection. At the same time, this paper postulates that the shift of other forms of relation with time towards «cultura» constitutes the double episteme of this original formula of domination. The test is structured in four parts:  1. A study of the relationship between writing and conquest; 2. A work on the link between the writing of history and the theory of sovereignty, between the writing of history and colonialism; 3. A study of the procedures that relegated in culture the  non-linear forms of relationship with time; 4. An approach of the mechanisms of historicism which prevent the thought of anachronism, asynchrony or repetition as subordinate historical logics.